PILATES: PHYSICAL THERAPY AS IMPROVING THE QUALITY OF LIFE IN ELDERLY (Fiep Bulletin - online, 2012)
The Pilates method is of fundamental importance in performing activities of daily living, especially in the elderly who seek independence in their daily optimizing, developing a new attitude and greater mobility, balance and agility while providing well-being, physical and mental. The aim of this paper was to investigate how the Pilates physical therapy in improving quality of life in the Elderly. Characterized as a qualitative research literature review. This research fills a gap, which can meet the requirements and lack both the health professionals as to academics and professionals in related fields, so that the elderly have been fortunate to conduct independent functions, how simple it is through physical activities using the Pilates method as a physical therapy resource. It is concluded that the performance of Pilates in elderly health is related to the ability to get a healthy aging, maintenance and improvement of cognitive function and prevent problems that may limit their functional capacity, and thus, perform their activities of daily living independent professionals and thereby improving their quality of life.
Keywords: Pilates; Elderly; and Quality of Life.